Joint village land use planning in Tanzania - CGIAR Research Program on Livestock (2018)
JVLUP was piloted in one cluster of villages, replicated in three more. Government has publicly supported on number of occasions. Incorporated into government guidelines and strategies. Collective group land titles to grazing lands been issued. Conflicts between land users resolved. Landscape level decision making tool developed. Influenced WPLUP in Ethiopia.